Modern management of malignant pleural mesothelioma - Patel SC (Dove Medical Press, 2016)
Shivani C Patel,1 Jonathan E Dowell1,2 1Division of Hematology and Oncology, University of Texas Southwestern, 2Section of Hematology and Oncology, Veterans Affairs North Texas Healthcare System, Dallas, TX, USA Abstract: Malignant pleural mesothelioma (MPM) is a deadly disease that produces a significant worldwide health care burden. The majority of cases are associated with prior asbestos exposure, but recent studies have identified a possible genetic predisposition in a minority of patients. Historically, obtaining a pathologic diagnosis of MPM was challenging, but with current pathological techniques, a secure diagnosis is possible in the majority of patients. Curative therapy for MPM remains elusive, and the primary treatment option for fit patients is platinum-based chemotherapy. Encouraging recent reports suggest that there may be a benefit to the addition of bevacizumab to standard chemotherapy as well as with the use of immune checkpoint inhibitors in MPM. Selected patients may be considered for aggressive surgical approaches, but there is considerable controversy regarding the true benefit of surgery and multimodality therapy in this disease. Keywords: mesothelioma, asbestos, chemotherapy, surgery